2020
DOI: 10.1002/ccd.29311
|View full text |Cite
|
Sign up to set email alerts
|

Validation of novel 3‐dimensional quantitative coronary angiography based software to calculate fractional flow reserve post stenting

Abstract: Objectives To validate novel dedicated 3D‐QCA based on the software to calculate post PCI vessel‐FFR (vFFR) in a consecutive series of patients, to assess the diagnostic accuracy, and to assess inter‐observer variability. Background Low post percutaneous coronary intervention (PCI) fractional flow reserve (FFR) predicts future adverse cardiac events. However, FFR assessment requires the insertion of a pressure wire in combination with the use of a hyperemic agent. Methods FAST POST study is an observational, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The feasibility and excellent diagnostic performance of angiography-based FFR may increase the adoption rate of coronary physiological assessment in real-world practice. In this context, angiography-based FFR may play a role in specific clinical settings, such as non-culprit lesion assessment in ST elevation myocardial infarction ( 14 , 17 ), post coronary stenting ( 18 , 19 ), risk stratification ( 20 ) or event adjudication in clinical trials ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility and excellent diagnostic performance of angiography-based FFR may increase the adoption rate of coronary physiological assessment in real-world practice. In this context, angiography-based FFR may play a role in specific clinical settings, such as non-culprit lesion assessment in ST elevation myocardial infarction ( 14 , 17 ), post coronary stenting ( 18 , 19 ), risk stratification ( 20 ) or event adjudication in clinical trials ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that caFFR measurement had a good correlation with wire-based FFR measurement both before and after PCI. Similarly, post-PCI QFR and vFFR measurements correlated reasonably well-with post-PCI wire-based FFR measurements (28,29). However, in a retrospective study of data collected by more than 50 centers, a weak correlation was reported between vFFR measurement and wire-based FFR measurement because of poor image quality and the difficulty tracking aortic pressure (30).…”
Section: Discussionmentioning
confidence: 72%
“…7 The FAST POST study demonstrated that the 3D-QCA derived post PCI vFFR correlates well with invasively measured microcatheter based FFR and has a high diagnostic accuracy to detect FFR <0.90 with low interobserver variability. 8 Another study demonstrated in patients with good quality angiographic visualization of left main coronary artery (LMCA), and available complete LMCA intravascular ultrasound (IVUS) footage, 3D-QCA based vFFR assessment of LMCA disease correlates well to LMCA minimum luminal area as assessed by IVUS. 9 The multicenter FAST (Fast Assessment of STenosis severity; NCT03791320) study, a prospective observational multicenter study designed to evaluate the diagnostic accuracy of offline 3D-QCA based FFR, using CAAS Workstation (Pie Medical Imaging, Maastricht, the Netherlands) in identifying hemodynamically significant CAD, compared with pressure-wire based FFR (≤0.80), is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%